Islam and the challenge of democracy - Abou El Fadl, Khaled 1963- (Princeton University Press, 2004)
The events of September 11 and the subsequent war on terrorism have provoked widespread discussion about the possibility of democracy in the Islamic world. This work aims to engage the reader in a discourse on the challenges of democracy in contemporary Islam.